STRATEGI PEMERINTAH DESA DALAM MENINGKATKAN DESTINASI WISATA “SAWAH LUNGGUH” UNTUK KESEJAHTERAAN MASYARAKAT DESA BARENG KECAMATAN PUDAK KABUPATEN PONOROGO - Yusuf Adam Hilman; Rosaria Hafsary Ngupadi Putri (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2022)
The Bareng Village Government develops the natural potential that exists with tourism-aware groups whose goals are for the welfare of the community. The purpose of this study is to describe the village government's strategy in improving Lungguh Sawah Tourism for the welfare of the people of Bareng Village, Pudak District, Ponorogo Regency. The method used in this research is descriptive qualitative method, the data used can be obtained from observation, in-depth interviews and documentation. This tourist village was developed to advance the Village Together in the economic, social and cultural fields. The results of this study are the strategies carried out by the Bareng village government to increase rice field tourism, which include promotion through social media, holding interesting activity events, adding attractive infrastructure, and having a friendly tourism awareness group.